Understanding sociology - Calhoun, Craig J., 1952-; Light, Donald, 1942-; Keller, Suzanne (New York : McGraw - Hill, 1995)
[The authors] have tried to make this a book students will want to read as well as a book from which they will learn about the best of contemporary and classical sociology.... The concepts of functional integration, power, social action, social structure, and culture are presented as major tools of sociological work.--Pref.
Study of sociology: Sociological perspective; Methods of sociological research; Culture; Interaction and social structure -- Individual and society: Socialization; Life course, from childhood to old age; Deviance and crime; Groups and organizations -- Inequality and power: Class and stratification; Race and ethnicity; Sex and gender -- Social institutions: Family; Education; Religion; Health and health care; Economics and work; Politics, the State, and war -- Global challenges: Third world; Population and environment; Communities and urbanization; Social movements and collective action; Social change -- Glossary.
Includes bibliographical references (p. [593]-618) and indexes.
Keywords: Sociology